THE EFFECT OF DIFFERENT AMOUNT OF SALT ADDED ON THE QUALITY OF TILAPIA FISH(Oreochromis niloticus)BEKASAM - Nahot Tua Sitohang; N Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aimed to observe the influence of the addition salt at the different concentrations on the quality of tilapia fish (Oreochromis niloticus) bekasam. The research method used was experimentalcomposed for non factorial complete randomized design (CRD). The treatment conducted was the addition salt at the different concentrations (5%, 10%, 15%, and 20%) in fish fermentation to produce bekasam. Parameters used in the study were sencory evaluation, pH, salt content, total plate number of bacteria, and total of lactic acid bacteria. The results showed that the highest quality of bekasam wasproduces by the addition of salt at concentration 15% of the fish weight. It was indicated by the highest organoleptic value, showed by the score of appearance (6.0) with interesting characteristics and brownish color, taste (6.1) with specific and typical tasteof fermented fish, odor (6.6) with the specific and typical taste of fermented fish odor, and distinctive features of texture (6.6) with chewy and solid textured. The chemical characteristics of the best bekasam were showing the calue of pH 4.64 and the content of salt 0.87. Meanwhile, the characteristics of microbiology were showing the total aerobic bacteria 2.2 x 104Cfu/ g and total lactic acid bacteria 3.5 x 105Cfu/ g.Keywords : Bekasam, Fermentation, Oreochromis niloticus, Salt